The Determinants of Learning English of Students with Visual Impairment: A Case at Universitas Negeri Padang - Nabila Ningra; Delvi Wahyuni (Universitas Negeri Padang, 2023)
In learning English there are factors that determine or are called determinants. This research was conducted at Padang State University to find out the determinants of learning English in children with visual impairments. There were seven respondents who were studying at Universitas Negeri Padang. This study was conducted with qualitative methods and using a questionnaire as a tool of data collection. The results of the study show that the determinants of learning English of students with visual impairment at Universitas Negeri Padang are aptitude, motivation and opportunity. Based on the research results, the percentage of respondents' answers for aptitude is 53%, then the percentage of respondents' answers for motivation is 71% and the percentage of answers for opportunity is 67%. This percentage is sufficient to answer that aptitude, motivation and opportunity are determinants in learning English for students with visual impairment at Padang State University.